Multiple doses of SHR-1222, a sclerostin monoclonal antibody, in postmenopausal women with osteoporosis: A randomized, double-blind, placebo-controlled, dose-escalation phase 1 trial - Dai, Zhijie; Zhu, Ronghua; Sheng, Zhifeng; Qin, Guijun; Luo, Xianghang; Qin, Qun; Song, Chunli; Li, Liping; Jin, Ping; Yang, Guoping; Cheng, Yanxiang; Peng, Danhong; et al. (Frontiers in Endocrinology, 2023)
SHR-1222, a novel humanized monoclonal antibody targeting sclerostin, has been shown to induce bone formation and decrease bone resorption at a single dose ranging 50–400 mg in our previous phase 1 trial. This study was a randomized, double-blind, placebo-controlled, dose-escalation phase 1 trial, which further investigated the safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD), and immunogenicity of multiple ascending doses of SHR-1222 in women with postmenopausal osteoporosis (POP). A total of 105 women with POP were enrolled and randomly assigned. Twenty-one received placebo and eighty-four received SHR-1222 sequentially (100 mg QM, n=4; 200 or 300 mg QM, n=20; and 400 or 600 mg Q2M, n=20). The most common adverse events included increased blood parathyroid hormone, increased low-density lipoprotein, increased blood alkaline phosphatase, increased blood cholesterol, back pain, and arthralgia, the majority of which were mild in severity without noticeable safety concerns. Serum SHR-1222 exposure (Cmax,ss and AUC0-tau,ss) increased in a greater than dose-proportional manner. Following multiple doses of SHR-1222, the bone formation markers (terminal propeptide of type I procollagen, bone-specific alkaline phosphatase, and osteocalcin) increased in a dose-dependent manner, whereas the bone resorption marker (β-C-telopeptide) was downregulated. Accordingly, BMD gains in the lumbar spine, total hip, and femoral neck were observed. The maximum BMD increase from baseline at the lumbar spine was detected in the 300 mg QM cohort (14.6% vs. 0.6% in the placebo group on day 169). Six (6/83; 7.2%) subjects developed anti-SHR-1222 antibodies with no discernible effects on PKs, PDs, and safety. Thus, multiple doses of SHR-1222 showed an acceptable safety profile and dose-dependent plasma exposure in women with POP, and could improve their BMD rapidly and prominently by promoting bone formation and inhibiting bone resorption. These findings further support SHR-1222 as a potential alternative agent for the treatment of POP.